Tinjauan Geografi dalam Pelaksanaan Pendidikan Seksual Pada Generasi Muda Indonesia - Syamsunardi, Syamsunardi; Syam, Nur (UNIVERSITAS NEGERI MAKASSAR, 2021)
Sexual education is one of the alternatives to smooth the path of Indonesia to reach the golden generation in the future by implementing sexual education for the younger generation can be done by changing the term Sexual Education into reproductive health education, family health education or gender education (gender). This research was conducted in Takalar Regency, South Sulawesi. This study aims to describe the strategy of implementing sexual education for the younger generation and know the purpose of sexual education for adolescents in Indonesia, especially in Takalar Regency. The research method used is qualitative study library. The results of this study show that it takes camouflage of the term sexual education so as not to make people amused or ashamed to listen to what the presenter says about sexual education. Camouflage of appropriate sexual education terms are reproductive health education, family health education or gender education (gender) as well as teaching sexual education with camouflage reproductive health education, family health education or gender education (gender) to prevent the younger generation from various negative things such as premarital sex among indonesian adolescents, especially in Takalar district.